Obstacles to NGOs' accountability to intended beneficiaries: the case of ActionAid. Issue 6 (17th August 2016) - Walsh, Sinead
ABSTRACT: While NGO accountability is widely discussed in the literature, there has been little work done on how accountability systems operate in practice. This article aims to address this gap by using qualitative empirical data to provide a case study of one NGO's initiative in this area. ActionAid has made substantial, high-profile efforts to improve its downward accountability since 2000. Using data from fieldwork conducted in Uganda and internationally, the article reveals the operational obstacles which have hindered ActionAid in its attempts to strengthen its accountability to intended beneficiaries at the community level, and reviews ActionAid's ongoing commitment to this goal.